2004
DOI: 10.1111/j.1529-8817.2003.00750.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular response to climate change: temperature dependence of UV‐induced DNA damage and repair in the freshwater crustacean Daphnia pulicaria

Abstract: In temperate lakes, asynchronous cycles in surface water temperatures and incident ultraviolet (UV) radiation expose aquatic organisms to damaging UV radiation at different temperatures. The enzyme systems that repair UV-induced DNA damage are temperature dependent, and thus potentially less effective at repairing DNA damage at lower temperatures. This hypothesis was tested by examining the levels of UV-induced DNA damage in the freshwater crustacean Daphnia pulicaria in the presence and absence of longer-wave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
136
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(150 citation statements)
references
References 35 publications
13
136
1
Order By: Relevance
“…In addition to pigmentation and vertical migration, zooplankton use other survival strategies as responses to UV radiation: for example, photo-enzymatic repair of DNA and screening substances like MAAs (MacFadyen et al 2004;Moeller et al 2005). Repair processes in copepods are reported by several authors, but the importance of these processes is not well understood (Zagarese et al 1997;Rocco et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to pigmentation and vertical migration, zooplankton use other survival strategies as responses to UV radiation: for example, photo-enzymatic repair of DNA and screening substances like MAAs (MacFadyen et al 2004;Moeller et al 2005). Repair processes in copepods are reported by several authors, but the importance of these processes is not well understood (Zagarese et al 1997;Rocco et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…UV radiation may penetrate deeply into clear waters (Kirk 1994), and several studies show that suppressed reproduction and increased mortality among zooplankton (Crustacea) can be attributed to UV exposure (Williamson et al 1994;Zagarese et al 1994;Leech and Williamson 2000). In defense, zooplankton have a number of different UV protection strategies, including cell repair systems, vertical migration, and photo-protective pigments (Hairston 1976;MacFadyen et al 2004;Hansson et al 2007). Photo-protective pigmentation among copepod zooplankton is induced by UV radiation, resulting in increased carotenoid pigmentation (Hansson 2000).…”
mentioning
confidence: 99%
“…These declines most likely result from a combination of physical habitat modification, point source pollution, sedimentation, invasive species, and warming temperatures due to climate change (as reviewed by Hastie et al, 2003). Warming trends have already caused alterations in thermal structure and water quality (Cruise et al, 2000; reviewed by Caissie, 2006), resulting in downstream effects on primary producers, migratory fishes and macroinvertebrates (Davis et al, 2013;Harper and Peckarsky, 2006;MacFadyen et al, 2004;O'Reilly et al, 2003;Winder et al, 2009). Ecosystem-level functional alteration may be especially pronounced within the state of Alabama, a renowned biodiversity hotspot for freshwater fauna, particularly fishes, crayfish and mollusks (Lydeard and Mayden, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…However, few multifactorial experiments have been dedicated to studying the effect of multiple global change stressors on aquatic ecosystems, and very few have studied the effects at several trophic levels. For example, it has been found that the effect of UVBR may be temperature dependent because temperature enhances photo-enzymatic repair (Williamson et al 2002;MacFadyen et al 2004). Another study (Doyle et al 2005) has shown that the effect of UVBR on phytoplankton growth is not only temperature dependent but also nutrient dependent.…”
mentioning
confidence: 99%